The Effect of Brand Image and Celebrity Influencers towards Consumer Purchase Intention of ERIGO Store - Phwa, Kanaya Audy; Putri, Maria Ervania Eka (Journal of Business, Management, and Social Studies, 2022)
Exacerbated by mass media and modern digital marketing, the role of celebrity influence is considered paramount in driving forward purchase intention and in building a strong brand image. However, studies for this topic provide mixed results, with very few being conducted within the geographical context of Indonesia. This paper surveys whether these factors (celebrity influence; brand image) significantly affect Indonesian respondents’ purchase decision for the local brand, ERIGO. An online survey questionnaire was developed using multiple perceptional scales with prevalidated survey items, as taken from previous research. The results show that neither brand image nor celebrity influence have a positive significant impact on purchase decision for respondents in Indonesia. The suggested consumer purchase intention study will contribute to the growing body of knowledge aimed at understanding behavior of consumer purchase intention in Indonesia.